Social Impact Bonds: Blockbuster or Flash in a Pan?. Issue 12 (14th October 2016) - Arena, Marika; Bengo, Irene; Calderini, Mario; Chiodo, Veronica
ABSTRACT: Despite the general hype, Social Impact Bonds' (SIB) rate of adoption is still modest. The mismatch between widespread interest and actual adoption raises interesting questions as to whether we are still in the early adoption phase of SIBs and massive diffusion is yet to come, or we are observing a marginal phenomenon. In order to shed some light on this issue, the paper provides a review of the cases in which the SIB model has been already applied, exploring the specific configuration employed, with the purpose to identify regular configuration patterns and their deviation from a prototypical structure.